(untitled) (Community Based Medical Journal, 2026)
A cross-sectional, descriptive study which was carried out in the Department of Anatomy, Mymensingh Medical College Mymensingh, Bangladesh, from January 2023 to December 2023, to measure talar facet of lower end of the dry human adult fibula in a Bangladeshi population. A total of 300 (right 152 and left 148) dry human fibula were selected through the purposive sampling technique. Any damaged, unossified, fractured fibula were excluded. The mean maximum lengths of talar facet of the lower end of fibula were found 19.60±2.18 mm and 19.76±1.90 mm on right and left side respectively. The mean diameter of the antero-medial border of talar facet on the right side was 18.58±2.04 mm and 18.83±2.20 mm on the left side. The mean diameter of the postero-medial border of talar facet on the right side was 18.84±2.07 mm and 19.16±2.31 mm on the left side. The mean diameter of the base of talar facet on the right side was 16.61±1.66 mm and 16.94±2.39 mm on the left side. Various osteometric measurements of the distal end of talar facet of the fibula bone are essential in considering the fixity of ankle joint in designing of prostheses for use in ankle anthroplasty and in interpretation of diagnostic analogy of the ankle joints. CBMJ 2026 January: vol. 15 no. 01 P:96-102